2020
DOI: 10.2166/wcc.2020.213
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of climate change compound indices in Iran

Abstract: The time-placement scheme of climate extreme changes is important. In this regard, a set of a compound index derived using daily resolution climatic time series data is examined to assess climate change in Iran. The compound indices were examined for 47 synoptic meteorological stations during 1981–2015. The results show that most stations experienced a negative trend for the cool/dry (CD) and cool/wet (CW) index and a positive trend in CW was observed in some dispersed small areas. Both warm/dry (WD) and warm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The increasing temperature was expected to increase evaporation rates, leading to higher humidity during the summer in this climate zone. Moreover, the significant increase in MDSL and its temperature, coupled with rainfall reduction, has resulted in drier and warmer climate conditions in the last 30 years compared to the past 60 years, consistent with the previous studies 79 .…”
Section: Resultssupporting
confidence: 91%
“…The increasing temperature was expected to increase evaporation rates, leading to higher humidity during the summer in this climate zone. Moreover, the significant increase in MDSL and its temperature, coupled with rainfall reduction, has resulted in drier and warmer climate conditions in the last 30 years compared to the past 60 years, consistent with the previous studies 79 .…”
Section: Resultssupporting
confidence: 91%
“…The analysis of the standard normal homogeneity test for temperature shows that among the examined 139 stations, 126 of the stations have breakpoints (Figure 2a), while for precipitation, only 33 stations have break points (Figure 2b). The results of many recent studies have shown that Iran has become warmer and drier in recent decades (e.g., Alizadeh-Choobari & Najafi, 2018;Roshani et al, 2021;Sotoudeheian et al, 2022), and we argue that the heterogeneity of the data could be caused by climate change.…”
Section: Homogeneity Testmentioning
confidence: 69%
“…The trees in this complex have been planted in two time periods in 2004 and 2010 with a distance of about 3 meters from each other. The region is cold semi-arid according to the Koppen climate classification system (Roshani et al, 2021) and has a relatively high slope in terms of topography (altitude from 1037 m to 1112 m) with average rainfall and temperature of 260 mm and 15 °C in a 10-year period (2010-2020) according to Bojnord Airport Meteorological Station (The station closest to the study area).. The main soil type of this park is silty clay and silty loam.…”
Section: Study Areamentioning
confidence: 99%